Evaluation of anticancer activity of celastrol liposomes in prostate cancer cells. (August 2014) - Wolfram, Joy; Suri, Krishna; Huang, Yi; Molinaro, Roberto; Borsoi, Carlotta; Scott, Bronwyn; Boom, Kathryn; Paolino, Donatella; Fresta, Massimo; Wang, Jianghua; Ferrari, Mauro; Celia, Christian; et al.
Abstract Context: Celastrol, a natural compound derived from the herb Tripterygium wilfordii, is known to have anticancer activity, but is not soluble in water. Objective: Formation of celastrol liposomes, to avoid the use of toxic solubilising agents. Materials and methods: Two different formulations of PEGylated celastrol liposomes were fabricated. Liposomal characteristics and serum stability were determined using dynamic light scattering. Drug entrapment efficacy and drug release were measured spectrophotometrically. Cellular internalisation and anticancer activity was measured in prostate cancer cells. Results: Liposomal celastrol displayed efficient serum stability, cellular internalisation and anticancer activity, comparable to that of the free drug reconstituted in dimethyl sulfoxide. Discussion and conclusion: Liposomal celastrol can decrease the viability of prostate cancer cells, while eliminating the need for toxic solubilising agents.